Improving the synthetic efficiency of single-wall carbon nanotube forests using a gas-analysis-designed mixed carbon feedstock. (December 2020) - Shibuya, Akiyoshi; Chen, Guohai; Miyoshi, Akira; Futaba, Don N.
Abstract: A high efficiency, mixed gas carbon feedstock was designed by gas analysis of ethylene-based single-wall carbon nanotube (SWCNT) chemical vapor deposition. Gas analysis identified acetylene and 1, 3-butadiene as the primary contributors to CNT growth based on the observed correlation between the decrease in respective concentrations and the CNT growth rate. In addition, a semi-empirical chemical kinetics growth model was developed which further verified that the experimentally observed decrease of acetylene and 1, 3-butadiene were due to their contribution to the synthesis reaction. Using these results, we designed a mixed carbon feedstock of acetylene and 1, 3-butadiene at a ratio of 2:5 which efficiently grew high purity and selectivity SWCNTs at a high growth efficiency, four-times that of pure ethylene and two-times that of pure acetylene. The combination of acetylene and 1, 3-butadiene proved synergetic due to the inherent differences in reactivity and hydrogen content through "carbon scavenging" by the hydrogen byproducts. As a result, unlike single-source carbon feedstocks, the total carbon feedstock concentration could be increased, which resulted in increasing yields without saturating the catalysts. Our results demonstrate the complementary roles of carbon feedstocks in developing high efficiency synthesis, which is important for the advancement of the synthesis of long and clean CNTs. Graphical abstract: Image 1 Highlights: High efficiency carbon nanotube synthesis mixed feedstock was designed. Key carbon species were identified by gas analysis and chemical kinetics simulation. The mixed carbon feedstock was composed of acetylene and 1, 3-butatidiene. Growth efficiency 4x higher than ethylene and 2x higher than acetylene.